A feasibility study on beef tallow conversion to some esters for biodiesel production - Mohamad Ali Ghazavi; Majid Fallahipanah; Hamed Shahmirzae Jeshvaghani (International Journal of Recycling of Organic Waste in Agriculture)
Background: Nowadays, management and recycling of industrial by-products are one of the most important issues in developing and developed countries. Beef tallow is one of these residues produced in slaughter houses and primarily is utilized in soap production industry. However, when this industry is overloaded, the extra fats are usually incinerated or disposed in a sanitary landfill. However, beef tallow may be consumed in biodiesel production. Therefore, in this work, the process of biodiesel production in a pilot plant has been studied using beef tallow as raw material with methanol and potassium hydroxide as catalyst. The quality of the produced biodiesel is evaluated using Fourier transform infrared spectroscopy (FTIR) method. Results: FTIR analysis showed that the final product contains ester compositions which can be used as biodiesel fuel in diesel engines. The viscosity of natural beef tallow was very high, and actually, it was solid; however, after transesterification the viscosity of the final product decreased, and it became liquid. The viscosity of the final product measured at 40°C was 5.3 mm2 s â1 , and the comparison of this biodiesel with the data of ASTMD-445 standard resulted in the similarity of this product with petroleum diesel (3 to 12 mm2 s â1 ). Conclusions: Alkaline transesterification of beef tallow with methanol decreases the viscosity of the final synthesized product and produces a high quality biodiesel for diesel engines. Beef tallow is one of the low cost residual materials available in slaughter houses. Therefore, the slaughter houses can be considered as one of the available sources to produce biodiesel. In this research, the process of biodiesel production from beef tallow was validated, but the economical viability must be improved by recovering methanol and glycerol.